UMBERTO ECO: MISTERI PROTOKOL TETUA YAHUDI, DAN MITOS MENGUASAI DUNIA - Media Zainul Bahri (Himpunan Peminat Ilmu-Ilmu Ushuluddin (HIPIUS), 2016)
This article elucidates a paradigm embedded in the memory of Indonesian Muslims about “Jewish conspiracies” or “the Protocols of the Elders of Zion” who want to rule the world. This paradigm became known as “Conspiracy theory”. First, this article will describe the views of Umberto Eco, a novelist, semioticist, and medieval European historian. Second, tracing books about the Jewish conspiracy that circulated among Muslims. Third, confronting conspiracy theories with facts and my subjective opinions. In the study of political sociology, conspiracy theory is a closed system that is unfalsifiable, and therefore “a matter of faith rather than proof”.It is hard to find solid evidence. Instead of preserving this absurd paradigm of conspiracy theory, Muslims should focus on developing the quality of their human resources. The human history has proven that superior nations who dominating the world are those who capable in managing human resources, regardless of their race, nation and religion.